The Synthesis and Optoelectronic Applications for Tellurophene‐Based Small Molecules and Polymers. Issue 20 (16th July 2019) - Wu, Xiaoxi; Lv, Lei; Hu, Lifang; Shi, Qinqin; Peng, Aidong; Huang, Hui
Abstract: Tellurophene‐based small molecules and polymers have received great attentions owing to their applications in thin‐film transistors, solar cells, and sensors. This article reviews the current progress of the synthesis and applications of tellurophene‐based small molecules and polymers. The physicochemical properties and optoelectronic applications of tellurophene‐based materials are summarized and discussed. In the end, the challenges and outlook of tellurophene‐based materials are presented. Abstract : Organic electronics : This mini review presents the recent progress of tellurophene‐based molecular and polymeric materials.